Biotechnological Approach for Development and Characterization of Protein Feed for Melipona quadrifasciata - Patrícia Miranda-Pinto; Jullio Kennedy Castro Soares; Irys Hany Lima Gonzalez; Yuri Ribeiro Diogo; Lívia Soman de Medeiros; Luciana Chagas Caperuto; Patrícia Locosque Ramos; Tiago Maurício Francoy; Michelle Manfrini Morais (Agriculture)
Stingless bees are vital pollinators in tropical and neotropical regions, emphasizing the need to conserve these species. However, resource scarcity, particularly pollen, during certain periods negatively impacts bee health and pollination efficiency. To address this, we developed a fermented protein feed using microorganisms from pollen of Melipona quadrifasciata, a species commonly found in the Brazilian Atlantic Forest. The fermented feed consisted of a protein bran mixture, sugar syrup, and an inoculant derived from species’ fermented pollen. To assess the feed quality, nutritional evaluation and metabolomic analyses were conducted (UHPLC/DAD-HRMS/MS and GC-MS). The metabolomic analysis identified 85 compounds in positive and 102 in negative ionization modes. Shared metabolites, such as isoquercetin and palatinose, highlighted similarities between the feed and natural fermented pollen. Laboratory tests with caged bees showed comparable consumption between the feed and fermented pollen with no statistical difference (mean: 0.067 g vs. 0.060 g; p = 0.53). The feed exhibited a favorable pH transition (5.30 pre-fermentation to 4.41 after the fermentation process) and remained stable for six months at ±2 °C. These findings demonstrate a biotechnological advance in stingless bee nutrition, offering a viable solution during resource scarcity and promoting the health of M. quadrifasciata.